Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/ijsa.12070
|View full text |Cite
|
Sign up to set email alerts
|

Fakability of Implicit and Explicit Measures of the Big Five: Research findings from organizational settings

Abstract: This study investigates the extent to which response distortion occur when implicit measures of personality traits are used in applied settings. Two groups composed of 58 security guards and 45 semiskilled workers, respectively, completed five Implicit Association Tests (IATs) for assessing the Big Five personality traits as a part of a personnel assessment program. They additionally completed a self-report measure of the same personality dimensions. Scores on the Big Five IATs and self-ratings of personality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 63 publications
1
38
0
3
Order By: Relevance
“…With regard to self‐concept of personality IATs, whether or not participants can control the outcome of the measurement task has most often been examined. More specifically, the difference in mean IAT‐effects was examined in faking versus controlled conditions (between‐ or within‐subject designs), or in participants who took part in a personnel assessment program versus volunteers (Vecchione, Dentale, Alessandri, & Barbaranelli, ). In these studies, it is hypothesized that the differences in explicit measures between the faking condition/personnel assessment program versus the control condition/volunteers would be larger compared to the differences in implicit measures of personality between both conditions/groups. whether implicit personality self‐concept measures can differentiate between two groups by measuring an aspect of the self‐concept which is known to differ between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to self‐concept of personality IATs, whether or not participants can control the outcome of the measurement task has most often been examined. More specifically, the difference in mean IAT‐effects was examined in faking versus controlled conditions (between‐ or within‐subject designs), or in participants who took part in a personnel assessment program versus volunteers (Vecchione, Dentale, Alessandri, & Barbaranelli, ). In these studies, it is hypothesized that the differences in explicit measures between the faking condition/personnel assessment program versus the control condition/volunteers would be larger compared to the differences in implicit measures of personality between both conditions/groups. whether implicit personality self‐concept measures can differentiate between two groups by measuring an aspect of the self‐concept which is known to differ between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…A measure of the implicit associations can be obtained computing the difference between the mean latencies of the first and the second combined block. Several studies showed that the IAT can be used successfully to assess attitudes, stereotypes, self-esteem, and personality traits, showing adequate levels of criterion validity (e.g., Greenwald, Poehlman, Uhlmann, & Banaji, 2009) and less proneness to impression management concerns than self-report measures, in both experimental (Fiedler & Bluemke, 2005) and real-life situations (Vecchione, Dentale, Alessandri, & Barbaranelli, 2014).…”
Section: Implicit Association Testmentioning
confidence: 99%
“…While CV information can be reviewed manually, CVs can be used to find suitable candidates for specific vacancies much faster with the help of CVs software (Hoek, 2017). By using appropriate software, it is possible to proactively detect unethical behavior of candidates in answering questions during the selection process (Jackson et al, 2000;Kubinger, 2009;McFarland et al, 2002;Vecchione et al, 2014).…”
Section: Discussionmentioning
confidence: 99%